HIV-Associated Peripheral Neuropathy and Antiretroviral Therapy: A Prospective Study from a Tertiary Care Centre in South India - Rao, Anagha (Journal of Clinical Research In HIV AIDS And Prevention, 2025)
Background Peripheral neuropathy (PN) is a common and debilitating complication in people living with HIV (PLHIV). While HIV itself contributes to neuropathy, certain antiretroviral therapy (ART) drugs, particularly nucleoside reverse transcriptase inhibitors (NRTIs) such as stavudine (d4T) and zidovudine (AZT), are known for their neurotoxic effects. Objectives To evaluate the impact of ART on HIV-associated peripheral neuropathy (HIV-PN) and to determine whether certain ART regimens increase the risk or severity of neuropathy. Materials and Methods A cross-sectional study was conducted among 158 HIV-positive patients. Neuropathy was diagnosed using clinical criteria, Total Neuropathy Score (TNS), and nerve conduction studies (NCS). Patients were grouped based on their ART regimen, and statistical analysis was performed to assess the association between ART type and peripheral neuropathy severity. Results It was noted that patients on older NRTIs (stavudine, zidovudine) had significantly higher rates of peripheral neuropathy (p=0.002) and tenofovir-based regimens were associated with lower peripheral neuropathy prevalence (p=0.01). There was a significant correlation between the duration of ART exposure and peripheral neuropathy severity (p<0.001), suggesting a cumulative neurotoxic effect. Conclusion Older ART regimens, particularly stavudine and zidovudine, significantly contribute to HIV-PN. The study supports the WHO recommendation to phase out neurotoxic ART and highlights the importance of early ART regimen optimisation to prevent long-term neurological complications.
Keywords: HIV; peripheral neuropathy; ART; NRTIs; d-drugs; neurotoxicity; nerve conduction studies